2015
DOI: 10.1021/acs.joc.5b00914
|View full text |Cite
|
Sign up to set email alerts
|

Nazarov Reactions Intercepted by (4 + 3) Cycloadditions with Oxygen-Substituted Dienes

Abstract: The oxyallyl cation intermediate from the Lewis acid mediated Nazarov reaction of an allenyl vinyl ketone was intercepted by acyclic, 2-silyloxy-substituted butadienes by highly regioselective (4 + 3) cycloadditions. Stereoselectivity was often modest, but in some instances steric interactions were responsible for high selectivity. The results are consistent with concerted (4 + 3) cycloadditions. In many instances, the (4 + 3) products were susceptible to fragmentation or rearrangement in the presence of the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…We propose that the mechanism involves alkyl migration of the oxyallyl cation intermediate to form a stabilized benzylic cation, followed by 1,2‐phenyl migration. This suggests that alternate pathways such as rearrangements, or oxyallyl cation trapping,, by excess diene or side products can account for the lower yield of product 6 , although we were unable to observe or isolate these products. We also looked at using the more Lewis acidic boron trichloride as a catalyst in an attempt to optimize the yield (Scheme b).…”
Section: Methodsmentioning
confidence: 76%
“…We propose that the mechanism involves alkyl migration of the oxyallyl cation intermediate to form a stabilized benzylic cation, followed by 1,2‐phenyl migration. This suggests that alternate pathways such as rearrangements, or oxyallyl cation trapping,, by excess diene or side products can account for the lower yield of product 6 , although we were unable to observe or isolate these products. We also looked at using the more Lewis acidic boron trichloride as a catalyst in an attempt to optimize the yield (Scheme b).…”
Section: Methodsmentioning
confidence: 76%
“…In the case of unsymmetrical diene nucleophiles, e.g., 1,3‐pentadiene, the electron‐donating terminal group is attacked by the allenyl group giving products 109a, b, d . Subsequent studies using quantum‐chemical calculations showed that the [3+4] cycloaddition can proceed according to both a concerted or a sequential mechanism …”
Section: Interrupted Nazarov‐type Reactionmentioning
confidence: 99%
“…Burnell and colleagues reported a different type of tandem reaction, in which Nazarov cyclization intermediate 27# , derived from the allenyl vinyl ketone 26 , was trapped by the activated diene 28 via the [4 + 3] cycloaddition and subsequent rearrangement of 29a to afford the cyclopentene derivative 30 in excellent yield (Figure ) 13…”
Section: Recent Trends In Nazarov Cyclizationmentioning
confidence: 99%